Practical Gram-Scale Synthesis of Either α- or β-Anomer of C-Vinyl Glycosides - Rouzier, Florian; Sillé, Rosanne; Nourry, Arnaud; Tessier, Arnaud; Pipelier, Muriel; Guillarme, Stéphane (Synthesis, 2019)
The synthesis C-vinyl glycosides, useful intermediates for the synthesis of C-glycoconjugates, was carried out on gram-scale by controlled reduction of the corresponding ethynyl derivatives in good to excellent yields in different carbohydrate series.
Keywords: C-glycosides; controlled reduction; alkynes; gram-scale